Hanoman Obong sebagai Ide Kreatif Penciptaan Night Light Shadow Box - Aqim Amral Hukmi (Mahesa Research Center, 2021)
Puppet is a culture of the Indonesian nation. Puppet stories originally developed during the Javanese Hindu era. Pewayangan has been appointed as a masterpiece of world culture by UNESCO on 7 November 2003 or the Masterpiece of Oral and Intangible Heritage of Humanity. One of the familiar characters in puppet stories is Hanoman. However, nowadays people, especially teenagers who call themselves millennials, are less interested in puppet stories. To introduce traditional culture to society and millennial adolescents as the younger generation, breakthroughs or new innovative ways are needed, one of which is media that is popular among young people, namely by making a room decoration lamp called the Night Light Shadow Box. The research method used is descriptive qualitative research methods. The research begins by exploring the Hanoman figure. Furthermore, developing the results of observations that have been made through the product design of the Night Light Shadow Box so as to produce creative products that are in accordance with the interests of the community and millennial youth. The purpose of this research is (1) to create creative products with Hanoman local content vision that can compete with foreign products. (2) can foster understanding and love of the community towards the local culture of the archipelago.